2022
DOI: 10.1186/s12903-022-02278-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health profile status and treatment needs in the Salvadoran elderly population: a cross-sectional study

Abstract: Introduction Older adults are a highly vulnerable group in their general health condition, including oral health that can be influenced by different factors, among them, changes in oral tissues inherent to the physiological processes of aging and by systemic condition. In El Salvador, it is a group that has received little attention at the public health level. Objective To determine the profile of the oral health status and treatment needs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
2
3
1
1
Order By: Relevance
“…In addition, our study showed that there was a significant positive correlation between age and the average DMFT and MT numbers, while there was a negative correlation between DT and FT numbers. This confirms the existence of a positive correlation between age and the intensity of caries and tooth loss [18,19,[29][30][31][32][33].…”
Section: Dental Statussupporting
confidence: 76%
See 3 more Smart Citations
“…In addition, our study showed that there was a significant positive correlation between age and the average DMFT and MT numbers, while there was a negative correlation between DT and FT numbers. This confirms the existence of a positive correlation between age and the intensity of caries and tooth loss [18,19,[29][30][31][32][33].…”
Section: Dental Statussupporting
confidence: 76%
“…Particularly noteworthy is the highest percentage of men (65.7%) characterized by improper oral hygiene, despite the fact that they were notified by letter about the scheduled dental examination. Similar results were obtained among senior citizens (aged 60-75) from Salvador using the simplified Oral Hygiene Index (OHI), where the percentage of men with poor oral hygiene was 67.8% [19].…”
Section: Oral Hygienesupporting
confidence: 61%
See 2 more Smart Citations
“…Ambas enfermedades son las principales causantes de la pérdida de dientes permanentes, congruente con lo anterior, la encuesta también revela que la pérdida dental aumenta con la edad, ya que en mayores de 60 años se reportó una media de 16.2 dientes perdidos 3 . Según el estudio sobre estado de salud bucal y necesidades de tratamiento en población adulta mayor, la pérdida dental puede afectar la calidad de vida y función masticatoria 4 .…”
Section: Introductionunclassified